Creativity, energy of the future: Global energy transitions and challenges in the light of the EROI indicator - Virág, Attila (Vezetéstudomány / Budapest Management Review, 2024)
„Deglobalization,” „blocking,” the livelihood crisis pointing to the „catabolism of capitalism” - expressions that are becoming increasingly popular within professional discourse. It is the author’s contention that an analysis of energy return on energy invested (EROI) at a level of abstraction higher than that of everyday empirical experience can illuminate the deeper connections of the increasingly intense and diverse crises experienced in recent years. He proposes the development or invention of an interpretative theoretical framework that can make the increasingly incomprehensible reality more narratable. The main claim is that the EROI-based approach sheds light on the fact that the symptoms of today’s crises are not necessarily independent indicators but may easily be consequences of a deeper energy-related context. The author suggests that through the interpretative reality-interpretation framework based on the EROI indicator, the interpreted reality places us at a particular crossroad, once again emphasizing the role of human creativity.